A rare case of primary urethral squamous cell carcinoma with solitary bone metastasis - Neha Ann Varghese; Boobathi Raja Gopal; Harshini Malarmani; Sathish Prabhu Pushparaj (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Primary urethral carcinomas are rare genitourinary malignancies and squamous cell carcinoma is a less common subtype. Presentation is often non-specific in urethral cancers. A single lytic skeletal metastasis is rare with urethral carcinomas, diagnosis of which is pivotal for prognosis and management necessitating biopsy confirmation. Case presentation We report the case of a 61-year-old male with pain and swelling in the penis without any skin lesions. MRI of pelvis revealed a mass in the corpus spongiosum infiltrating the left corpus cavernosum which on biopsy confirmed to be squamous cell carcinoma. Further evaluation with PET-CT revealed a solitary lytic lesion in the left ischial bone with increased FDG uptake, which on CT-guided biopsy proved to be metastasis. Conclusion While penile squamous cell carcinomas commonly present as ulcers or ulceroproliferative growths originating from the penile skin or foreskin, an exophytically growing squamous cell carcinoma centred in the corpus spongiosum without any skin ulceration is a rare presentation of urethral malignancy. MRI, being exceptional in delineating the anatomy of penis and urethra, can give a possible solution to the origin of an advanced penile mass, which in our case pointed towards a primary urethral carcinoma. Histological diagnosis of solitary bone metastasis is also imperative as it has a significant prognostic value guiding further management.